My journey through marketingland. (29th May 2019) - Gummesson, Evert
Abstract : Purpose: The purpose of this viewpoint is to analyze and interpret the author's career as a researcher in marketing. Design/methodology/approach: This viewpoint applies case theory (Gummesson, 2017a), in which the author is the case. Findings: One should respect the difficulty of understanding the complex and dynamic world of marketing and not be fooled into premature generalizations and reverence to established theory. Originality/value: The emphasis is on marketing as a revenue-generating activity through interaction in the network of complex relationships; the need for less ritualistic research methodology; and the orientation toward theory generation, decision-making, implementation and achievement of desired results.